About complex intelligent technologies for techno-ecological events control in the water area - Pisarenko, V.G.; Nogin, N.V.; Kryachok, A.S.; Pisarenko, J.V.; Varava, I.A.; Koval, A.S. (Проблеми програмування, 2022)
Aspects of the important task solution of creating complex intelligent decision-making support technologies for the identification of techno-ecological event (TEE) and the optimal selection of the sequence of available measures to reduce the life cycle of this TEE in the water area in order to minimize material losses are considered ("CONTROL_TEE" system). In the V.M. Glushkov Institute of Cybernetics of NAS of Ukraine, Concern "BaltRobotics" (Ukraine-Poland), NTU of Ukraine "Igor Sikorsky KPI" study of the possibility of theoretical development, research and practical implementation of methods and tools that make up the information technology of research design (informational, mathematical, algorithmic, software, technical, organizational support) of robots intended for reconnaissance and neutralization of TEE in a number of environment. For the classifying waves, mathematical models of the propagation of both running and standing waves in the sea area were obtained and solved. The structure of the information storage of the situation center has been developed. In order to create a database wave classification and mathematical and computer modeling were carried out. The deterministic process of sound propagation in a flat waveguide in the homogeneous mode is considered. Special boundary value problems and Cauchy problems are solved for the two-dimensional wave equation and, accordingly, for the Helmholtz equation. Calculation formulas for sound pressure and corresponding to its velocities are obtained in an analytical closed form. In the general case, the tangent and normal components of the velocity vector and the hydrodynamic potential are calculated in the form of Fourier series by the methodology of the works of Bilonosov, Ovsienko, Li, Zinchenko, Zinchenko, Nogin. Розглядаються аспекти, що стосуються вирішення важливого завдання створення комплексних інтелектуальних технологій підтримки прийняття рішень для ідентифікації виникаючої техно-екологічної події (ТЕП) та оптимального вибору послідовності доступних заходів зі скорочення життєвого циклу даного ТЕП в акваторії з метою мінімізації матеріальних збитків (створення системи «УПРАВЛІННЯ_ТЕП»). В Інституті кібернетики імені В.М. Глушкова НАНУ сумісно з Концерном «BaltRobotics» (Україна – Польща), НТУУ «КПІ ім. Ігоря Сікорського» проводяться вивчення питання можливості теоретичної розробки, дослідження та практичної реалізації методів і засобів, що складають інформаційну технологію дослідницького проектування (інформаційне, математичне, алгоритмічне, програмне, технічне, організаційне забезпечення) інтелектуалізованих роботів, призначених для розвідки і нейтралізації небезпечних ТЕП у ряді середовищ. Для завдання класифікації хвиль отримано і вирішено математичні моделі поширення, як хвиль, що біжать, так і стоять, в акваторії моря. Розроблено структуру сховища інформації ситуаційного центру. Для створення бази даних інформаційного сховища ситуаційного центру було проведено класифікацію хвиль та відповідне математичне та комп’ютерне моделювання. Розглянуто детермінований процес поширення звуку в плоскому хвилеводі в однорідному режимі. Вирішено спеціальні крайові завдання та завдання Коші для двовимірного хвильового рівняння, і, відповідно, для рівняння Гельмгольця. В аналітичному замкнутому вигляді отримані розрахункові формули для звукового тиску і відповідно до його швидкостей. У загальному випадку за методикою робіт Білоносова, Овсієнка, Лі, Зінченка, Ногіна обчислено у вигляді рядів Фур’є дотичну і нормальну компоненти вектору швидкості і гідродинамічний потенціал.